Role and Posttranslational Regulation of Cx46 Hemichannels and Gap Junction Channels in the Eye Lens - Retamal, Mauricio A.; Altenberg, Guillermo A. (Frontiers in Physiology, 2022)
Connexins are a family of proteins that can form two distinct types of channels: hemichannels and gap junction channels. Hemichannels are composed of six connexin subunits and when open allow for exchanges between the cytoplasm and the extracellular milieu. Gap junction channels are formed by head-to-head docking of two hemichannels in series, each one originating from one of two adjacent cells. These channels allow for exchanges between the cytoplasms of contacting cells. The lens is a transparent structure located in the eye that focuses light on the retina. The transparency of the lens depends on its lack of blood irrigation and the absence of organelles in its cells. To survive such complex metabolic scenario, lens cells express Cx43, Cx46 and Cx50, three connexins isoforms that form hemichannels and gap junction channels that allow for metabolic cooperation between lens cells. This review focuses on the roles of Cx46 hemichannels and gap junction channels in the lens under physiological conditions and in the formation of cataracts, with emphasis on the modulation by posttranslational modifications.